(untitled) (Swiss Medical Weekly, 2010)
Deficiencies in collaboration and communication between healthcare professionals have a negative impact on the provision of healthcare and on patient outcomes. Policymakers and healthcare managers, as well as clinicians and practitioners, are aware of this and have a growing interest in improving these relationships. To establish new models of care delivery, it is necessary to determine the interventions that are most effective in furthering interprofessional collaboration. This article provides an overview of the evidence base for interprofessional collaboration involving doctors and nurses and new models of care in relation to patient outcomes. Two authors conducted independent literature searches in PubMed, CINAHL, and Cochrane Library and selected fourteen randomised controlled trials (RCT) for review. All of the RCTs originated from Western countries, and the majority tested collaborative care management models against usual care within the elderly population. The major components of the interventions involved individual evidence-based treatment plans, care coordination, health status monitoring, coaching in self-management and promotion of community-based services. They varied between a few days’ and three years’ duration. Outcome measures incorporated mortality, clinical, functional and social outcomes, and utilisation of medical services. Some studies also used patient-reported outcomes. While the results of the fourteen RCTs included were mixed, all but one study reported at least one statistically significant improvement in outcome following interventions based on interprofessional collaboration. More rigorous research in this field and expansion of areas of interprofessional collaboration are needed. Nevertheless, up to now the evidence base of interprofessional collaboration shows promising results in relation to patient outcomes.